Milling of Austempered Ductile Iron (ADI) with recycled carbide tools. Issue 1 (January 2016) - Priarone, Paolo; Robiglio, Matteo; Settineri, Luca
Abstract Ductile iron with austenitic-ferritic matrix (ADI), due to the specific heat treatment, shows an advantageous combination of engineering properties. The superior wear resistance and strength-to-weight ratio, together with high stress resistance and good ductility, make such material suitable for cost- and weight-efficient automotive structural applications. In this paper, results of milling experimental trials carried out on ADI 1200 are discussed. Tests were performed using uncoated and titanium aluminium nitride (TiAlN) or titanium carbo-nitride (TiCN)-coated cutting inserts obtained from both recycled and traditionally prepared tungsten carbide-cobalt (WC-Co)-based materials. Results show that satisfactory milling performance was obtained even by using recycled cutting materials, particularly when coated.